A novel steering-by-wire system with road sense adaptive friction compensation. (15th April 2022) - Liang, Xiutian; Zhao, Linfeng; Wang, Qidong; Chen, Wuwei; Xia, Guang; Hu, Jinfang; Jiang, Pengfei
Highlights: A novel steer-by-wire system with road sense compensation is presented. The road sense torque value are investigated and designed. An adaptive friction compensation controller is designed to track the torque. A double closed-loop system is designed to improve the stability and robustness. The HIL and vehicle experiment verify the effectiveness of the controller proposed. Abstract: This paper proposes an adaptive friction torque compensation scheme for the vehicle steer-by-wire (SBW) system. Firstly, the overall system structure is analyzed into a steering wheel subsystem and an active steering subsystem. Specifically, the road sense torque of the SBW system is represented by a plant model from the road sense motor input current to the steering wheel torque. Next, a road torque expression related to vehicle speed and road conditions is designed for the steering wheel subsystem. Furthermore, the torque expression has been corrected using damping model and coulomb friction model. Then, an adaptive friction compensation controller is designed for the SBW system, which adopts a LuGre dual observer and backstepping method (BS) to improve tracking accuracy by dealing with complex friction parameters estimation problems, and use an adaptive sliding mode control (SMC) component to deal with external disturbance and chattering. The stability and robustness of the adaptive friction compensation control system are verified through Lyapunov and frequency domain analysis. Finally, numerical simulations, hardware-in-the-loop (HIL) and vehicle experiments are carried out under various conditions. Numerical and experimental results demonstrate that the designed road sense conforms to the operating standard, and the proposed adaptive friction compensation controller has not only high compensation tracking accuracy but also high robustness. The proposed approach effectively reduces the steering wheel torque fluctuation caused by the mechanical friction, and can adaptively match different actuators.